Patterns of the Organizational Structure and its Impact in Meeting the Requirements of the Learn Organization: Applied Research in the Distribution Company of Oil Products in Basra - Ibrahim Mousa, Wisam; Jawad Kadhim Al-msary, Ameer; Hussein Ali, Oday (International Journal of Psychosocial Rehabilitation, 2020)
Modern business organizations strive to achieve the best performance through the use of modern methods in management science. Hence, they could achieve a position in the local and global markets in light of competition in the labor market. Furthermore, the organizational structure of business organizations is one of the most important pillars of them, which contribute to the distribution of powers and tasks; representation of authority; a nature of internal and external communication; and the vertical and horizontal expansion of routine procedures to facilitate work. Business organizations are currently seeking to reach their position as an educational institution based on modern management technologies to meet their needs, address their problems, and achieve customer satisfaction. The current study results found that there is a clear and positive correlation to the organizational structure and its various forms in achieving the requirements and aspirations of the educational institution.